Formononetin Ameliorates Cognitive Disorder via PGC-1α Pathway in Neuroinflammation Conditions in High-Fat Diet-Induced Mice - Fu, Xinxin; Qin, Tingting; Yu, Jiayu; Jiao, Jie; Ma, Zhanqiang; Fu, Qiang; Deng, Xueyang; Ma, Shiping (CNS & Neurological Disorders - Drug Targets, 2019)
Background: Alzheimer’s disease is one of the most common neurodegenerative diseases in many modern societies. The core pathogenesis of Alzheimer’s disease includes the aggregation of hyperphosphorylated Tau and abnormal Amyloid-β generation. In addition, previous studies have shown that neuroinflammation is one of the pathogenesis of Alzheimer’s disease. Formononetin, an isoflavone compound extracted from Trifolium pratense L., has been found to have various properties including anti-obesity, anti-inflammation, and neuroprotective effects. But there are very few studies on the treatment of Alzheimer’s disease with Formononetin. Objective: The present study focused on the protective activities of Formononetin on a high-fat dietinduced cognitive decline and explored the underlying mechanisms. Methods: Mice were fed with HFD for 10 weeks and intragastric administrated daily with metformin (300 mg/kg) and Formononetin (20 and 40 mg/kg). Results: We found that Formononetin (20, 40 mg/kg) significantly attenuated the learning and memory deficits companied by weight improvement and decreased the levels of blood glucose, total cholesterol and triglyceride in high-fat diet-induced mice. Meanwhile, we observed high-fat diet significantly caused the Tau hyperphosphorylation in the hippocampus of mice, whereas Formononetin reversed this effect. Additionally, Formononetin markedly reduced the levels of inflammation cytokines IL-1β and TNF-α in high-fat diet-induced mice. The mechanism study showed that Formononetin suppressed the pro-inflammatory NF-ΚB signaling and enhanced the anti-inflammatory Nrf-2/HO-1 signaling, which might be related to the regulation of PGC-1α in the hippocampus of high-fat diet -induced mice. Conclusion: Taken together, our results showed that Formononetin could improve the cognitive function by inhibiting neuroinflammation, which is attributed to the regulation of PGC-1α pathway in HFD-induced mice.
Keywords: Alzheimer' s disease